New approaches to EU foreign policy - Wilga, Maciej; Karolewski, Ireneusz Paweł (Routledge advances in European politics, 2014)
EU foreign policy once existed in the form of the European Political Cooperation with only a limited political leverage and symbolic institutional underpinnings. In recent years rapid changes have occurred, including an expanding institutional apparatus, increased responsibility and growing demand for action. This book examines new approaches to the EU's foreign policy that address its rapidly changing character, presenting the newest theoretical perspectives and dealing with novel empirical developments. Rather than simply considering structural variations and changes in the agency of the EU, it explores the new complexity in EU foreign policy.